Uncertainties in Sandy Shorelines Evolution under the Bruun Rule Assumption - Le Cozannet, Gonéri; Oliveros, Carlos; Castelle, Bruno; Garcin, Manuel; Idier, Déborah; Pedreros, Rodrigo; Rohmer, Jeremy (Frontiers in Marine Science, 2016)
In the current practice of sandy shoreline change assessments, the local sedimentary budget is evaluated using the sediment balance equation, that is, by summing the contributions of longshore and cross-shore processes. The contribution of future sea-level rise induced by climate change is usually obtained using the Bruun rule, which assumes that the shoreline retreat is equal to the change of sea-level divided by the slope of the upper shoreface. However, it remains unsure that this approach is appropriate to account for the impacts of future sea-level rise. This is due to the lack of relevant observations to validate the Bruun rule under the expected sea-level rise rates. To address this issue, this article estimates the coastal settings and period of time under which the use of the Bruun rule could be (in)validated, in the case of wave-exposed gently-sloping sandy beaches. Using the sedimentary budgets of Stive (2004) and probabilistic sea-level rise scenarios based on IPCC, we provide shoreline change projections that account for all uncertain hydrosedimentary processes affecting idealized low- and high-energy coasts. Hence, we incorporate uncertainties regarding the impacts of longshore processes, sea-level rise, storms, aeolian, and other cross-shore processes. We evaluate the relative importance of each source of uncertainties in the sediment balance equation using a global sensitivity analysis. For scenario RCP 6.0 and 8.5 and in the absence of coastal defenses, the model predicts a perceivable shift toward generalized beach erosion by the middle of the 21st century. In contrast, the model predictions are unlikely to differ from the current situation in case of scenario RCP 2.6. Finally, the contribution of sea-level rise and climate change scenarios to sandy shoreline change projections uncertainties increases with time during the 21st century. Our results have three primary implications for coastal settings similar to those provided described in Stive (2004) : first, the validation of the Bruun rule will not necessarily be possible under scenario RCP 2.6. Second, even if the Bruun rule is assumed valid, the uncertainties around average values are large. Finally, despite these uncertainties, the Bruun rule predicts rapid shoreline retreat of sandy coasts during the second half of the 21st century, if greenhouse gas concentration in the atmosphere are not drastically reduced (scenarios RCP 4.5, 6.0, and 8.5).